Pengaruh Sustainability Reporting, Intellectual Capital Terhadap Nilai Perusahaan Dengan Komite Audit Sebagai Moderasi - Herawati Dwi Wulandari; Suwarno, Suwarno (Universitas Muhammadiyah Gresik, 2025)
This study aims to analyze the effect of sustainability reporting and intellectual capital on firm value with the audit committee as a moderating variable. The population in this study consists of mining companies in the energy sector listed on the Indonesia Stock Exchange in 2020-2023. With the purposive sampling method, a sample of 32 companies (128 observation data) was obtained. The analysis method used is multiple linear regression using the SmartPLS 4 Program. The results of this study indicate that sustainability reporting significant negative effect on firm value, intellectual capital has an insignificant effect on firm value, the audit committee is unable to moderate the relationship between sustainability reporting and intellectual capital on firm value.